Digital Innovation Strategies to Enhance Competitive Advantage - Putri Putri; Yeye Suhaety; Fahrul Mauzu (Advances in Management & Financial Reporting, 2026)
Purpose: This study aims to analyze the digital innovation strategies implemented by Limitha Store to enhance its competitive advantage, identify their impact on business growth, and determine the challenges involved in their implementation. Research Method: This study employed a qualitative case study design. Data were collected through interviews, observations, and documentation from six informants (purposive sampling) and were then analyzed using the Miles, Huberman, and Saldaña model. Results and Discussion: The use of social media, QRIS payments, the real-picture promotional concept, and responsive (fast-response) service have significantly enhanced competitive advantage. This transformation has expanded the market and significantly increased sales by up to 300% (from an average of Rp20,000,000 to Rp80,000,000 per month). Technical challenges include unstable internet connections and delays in payment notifications. Implications: Retail MSME operators are advised to continue optimizing their operations using digital point-of-sale systems and to train their employees to develop their skills. Further research is recommended to examine the effectiveness of social media platforms specifically. Originality: This study fills a research gap by presenting an in-depth qualitative exploration of the dynamics of implementation and tactics of digital innovation among MSMEs in the ecosystem of a developing rural region.